Girls and Boys Have a Different Cardiometabolic Response to Obesity Treatment - Dalla Valle, Marketta; Laatikainen, Tiina; Potinkara, Hanna; Nykänen, Päivi; Jääskeläinen, Jarmo (Frontiers in Endocrinology, 2018)
Background: Childhood obesity exposes individuals to cardiometabolic disturbances. We analyzed how family-based multidisciplinary obesity treatment influenced children's cardiometabolic health. Materials and methods: In this retrospective, two-year, follow-up study of 654 2- to 18-year-old children treated for obesity in three Finnish pediatric clinics in 2005–2012, blood pressure (BP), metabolic parameters, and the influence of sex, puberty and a change in body mass index standard deviation score (BMI SDS) were analyzed. Results: At baseline, at least one cardiovascular risk factor was present in 474 (80%) cases. Boys presented with more significant changes in cardiometabolic parameters than girls during the treatment. Boys' total cholesterol (TC) improved by 12 months (P = 0.009), and their low-density lipoprotein C (LDL-C) and glycosylated hemoglobin ameliorated by 12 months (P = 0.030 and 0.022, respectively) and 24 months (P = 0.043 and 0.025, respectively). Boys' triglycerides, insulin, homeostasis model assessment for insulin resistance (HOMA-IR) and systolic BP deteriorated at 24 months (P < 0.001, 0.004, 0.002, and 0.037, respectively). In all children, the number of acceptable TC, LDL-C, insulin, and HOMA-IR values increased if BMI SDS reduced 0.25 or more by 12 months. Conclusion: Minor cardiometabolic improvements were found during the obesity treatment. These findings indicate the need to assess treatment methods and focus on prevention.